Прощай, предатель: повести / Сергей Алтынов - Алтынов Сергей Евгеньевич (Никто, кроме нас!)
Экземпляры: ф.23 (2007) / Инвентарный номер: 50469 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 52 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44